Sublingual piroxicam in the management of postoperative pain after surgical removal of impacted mandibular third molar - Shadab Mohammad; Vibha Singh; Puneet Wadhwani; Himanshu P Tayade; Onkar K Rathod (Wolters Kluwer Medknow Publications, 2012)
Introduction: Surgical removal of impacted mandibular third molar is one of the most commonly performed procedures in oral and maxillofacial surgical practice. The role of preoperative and postoperative medications for management of postoperative complications has been extensively evaluated. Aim: To assess the therapeutic effect of a single dose of 40 mg sublingual piroxicam (study group) vs 150 mg oral diclofenac (50 mg thrice a day) (control group) in patients undergoing surgical removal of impacted mandibular third molar. Materials and Methods: A total of 100 patients with asymptomatic impacted mandibular third molars were randomized into two groups. One group received two 20-mg tablets of piroxicam once daily on the first and second postoperative days, followed by one 20-mg tablet on the third post-operative day. The other group received one tablet of diclofenac 50 mg orally thrice daily on the first, second, and third post-operative days. Repeated extraoral examinations were done for continuous assessment of swelling, trismus, and reduction in pain. Ovearall impression of the treating physician and the patient regarding efficacy of study drugs were recorded at the end of the study. Results: In the piroxicam group there was >50% reduction in pain on all three days postoperatively. The incidence of swelling and trismus was found to be higher in the control group as compared to the study group. Adverse events, such as gastrointestinal (GI) disturbances, were significantly higher in the diclofenac group (11%) as compared to the piroxicam group (0%). Conclusion: Two sublingual piroxicam 20 mg tablets once daily has better efficacy and tolerability profile than diclofenac 50 mg one tablet thrice daily in the management of pain after surgical removal of impacted mandibular third molar. Study Title: A Comparative Study to Evaluate Clinical Efficacy and Safety of Sublingual Piroxicam and Diclofenac in the Management of Pain after Surgical Removal of Impacted Mandibular Third Molar.